An Unexpected Presentation of Haemoperitoneum in a Pregnant Woman. (23rd February 2015) - Arulpragasam, Kaushalya; Atkinson, Andrea; Epee-Bekima, Mathias
Abstract : In the majority of tertiary centres the Emergency Room or Assessment Unit is the gateway to the rest of the hospital. It is the location where critical decisions are formulated depending on whether a patient's condition is serious enough to warrant admission and, at times, emergency surgery. On occasion this decision can be straightforward based solely on the patient's presentation, observations, and basic investigations. This case highlights that although the decision and initial management may be apparent, often the diagnosis can be unexpected and that the diagnostic challenge is often outside the scope of a brief Emergency Room assessment. Corpus luteal cyst rupture is a common phenomenon but often not the cause of significant morbidity as it was in this case, especially in the absence of any associated risk factors.